Understanding the barriers to lifelong learning - a qualitative approach / Kardina Kamaruddin and Gopala Krishnan Sekharan Nair - Kamaruddin, Kardina; Sekharan Nair, Gopala Krishnan (2007)
This paper addressed issues relating to barriers to lifelong learning in an organization. By identifying the barriers, only then we could understand the motivation factors for learners to participate in lifelong learning activities. The context of the discussion was research and learning with respect to lecturers within higher education; specifically UiTM Terengganu. A definition of lifelong learning and professional development was given, and used to explain how it may contribute to the process of learning and research. Considering research as part of learning helped the discussion. Underpinning the discussion was the premise that research activities were essential to the role of lecturers, and had significant implications for lifelong learning for those involved in higher education. This paper objective was achieved by examining the barriers to learning in terms of the organization environment, motivation and personal needs. Specifically, this research investigated: 1. the work settings and learning 2. motivational orientations of learners and learning 3. the personal demands of learners and learning 4. the reason learners participate in learning This research was carried out qualitatively. Selected lecturers were interviewed and their responses were recorded, transcribed, interpreted, and analyzed based on the theme(s) of the research. Data(s) were collected through an in-depth, open-ended interview method. This research found that barriers to learning could be recognized from the internal and external perspectives. Internal issues such as personal motives, lifestyle issues and perceptions of learners relate to why'learners did not participate in learning. In addition, external issues such as job related motives, skills related motives, relationship/family motives, educational progressive motives, learning styles options, learning issues and progression issues contribute to fewer participants in the learning activities.